Molecular evidence for the adaptive evolution of Geobacter sulfurreducens to perform dissimilatory iron reduction in natural environments. Issue 4 (30th December 2019) - Liu, Xing; Ye, Yin; Xiao, Ke; Rensing, Christopher; Zhou, Shungui
Abstract: The electrically conductive pili (e‐pili) of Geobacter species enable extracellular electron transfer to insoluble metallic minerals, electrodes and other microbial species, which confers biogeochemical significance and global prevalence on Geobacter in diverse anaerobic environments. E‐pili are constructed by truncated PilA which is considered to have evolved from full‐length pilin by gene fission under positive evolutionary selection. However, this hypothesis is based on phylogenetic analysis and has not yet been experimentally confirmed. Here, we reconstructed an ancestral strain of G. sulfurreducens (designated COMB) carrying full‐length PilA by combining genes GSU1496 and GSU1497. The results demonstrated that strain COMB expressed and assembled the full‐length fused PilA and exhibited an outer membrane c ‐type cytochrome profile similar to the wild‐type strain. Surprisingly, the generated COMB‐pili were also conductive, indicating the evolution of truncated PilA did not occur for conductivity. Moreover, strain COMB minimally reduced Fe(III) oxides but maintained its ability to respire electrodes, demonstrating the truncation of pilin enables iron respiration. This study provides the first experimental evidence that the truncation of pilin in Geobacter species confers adaption to Fe(III)‐mineral‐mediated selective pressures, and suggests an evolutionary event during which the separation of the GSU1497 gene helped Geobacter survive and thrive in natural environments. Abstract : Geobacter speices have evolved variety of ways to respire iron oxides. Among them, the conductivity of pili has been thought to be a recently evolved feature and is necessary for iron oxide reduction in Geobacter sulfurreducens . The study reported here constructed the ancestral G. sulfurreducens strain expressing full‐length pilin, and demonstrated that the ancestral pilin also can construct conductive pili but cannot contribute the extracellular electron transfer to reduce iron oxides.